Perbandingan Kepuasan Menonton Film Miracle in Cell No. 7 Versi Korea dan Indonesia - Adnya Suari, Putu Krisnia; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2024)
Film remake is the art of giving a film a new look without changing the value of the original film. Remaking films is believed to help production companies make more efficient use of time and process when producing new films. Miracle in Cell No. 7 is a South Korean film, successfully remade by Indonesia, which tells the story of people with intellectual disabilities who are accused of raping and killing a girl, the daughter of a state official. The aim of this study is to measure the satisfaction of watching Miracle in Cell No. 7 Korean and Indonesian versions, using the uses and gratification theory with descriptive quantitative research methods. The results of this study suggest that there are differences in visual satisfaction due to the different values of the average gratification sought and obtained. However, the average of the individual indicators is in the “satisfied” to “very satisfied” category